Pendampingan Pajak UMKM: Masalah dan Solusinya - Amelia Sandra; Hanif Hanif; Rizka Indri Arfianti; Prima Apriwenni (President University, 2019)
Training on Income Tax Knowledge for MSMEs is the one step to improve the entrepreneurs’ taxation ability, as the members of the UPK PPUKMP Pulo Gadung East Jakarta. This training was held on 17 - 25 January 2019. Training instructors are lecturers who have a knowledge, expertise, and experience in fostering students. The purpose of this training, especially for entrepreneurs is to improve their simple accounting skills and taxation administration and other aspects related to it. The training process begins with a preparation by analyzing training needs, formulating training objectives, preparing material and conducting training. The training is carried out by giving lectures, discussions, question and answer, and audio-visual presentation. The results of this training are expected to increase technical knowledge for entrepreneurs in understanding their tax obligations, namely how to fill SPT, especially income tax for MSMEs and tax administration that should be done.